2020
DOI: 10.1097/sla.0000000000004482
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatobiliary Maljunction-associated Gallbladder Cancer Is as Common in the West, Shows Distinct Clinicopathologic Characteristics and Offers an Invaluable Model for Anatomy-induced Reflux-associated Physio-chemical Carcinogenesis

Abstract: Objective:To determine the associations of pancreatobiliary maljunction (PBM) in the West.Background:PBM (anomalous union of common bile duct and pancreatic duct) is mostly regarded as an Asian-only disorder, with 200X risk of gallbladder cancer (GBc), attributed to reflux of pancreatic enzymes. Methods: Radiologic images of 840 patients in the US who underwent pancreatobiliary resections were reviewed for PBM and contrasted with 171 GBC cases from Japan.Results:Eight % of the US GBCs (24/300) had PBM (similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
(76 reference statements)
1
24
0
2
Order By: Relevance
“…All of these together point to the milieu of this relatively small region, where 3 physiologically distinct environments converge, as the culprit for the development of these cancers. Other external observations that lend further credence to this include the established etiopathogenetic association of other anatomic variations such as pancreatobiliary maljunction (supra-Oddi union of common bile duct with main pancreatic duct), leading to reflux and causing cancers of the gallbladder, bile ducts and pancreas 18,19,28,34 as well as the well-known anatomic association of gastro-esophageal junction cancers developing through reflux and Barrett metaplasia. This is also supported by the fact that "transitional" zones where different epithelial types and milieus converge (as in the peri-ampullary region) are particularly vulnerable to chemical alterations as is well known for endoectocervical transition zone in the uterus and hilar lung cancers where transformation of respiratory to squamous epithelium takes place.…”
Section: Association Of Low Union With Peri-ampullary Cancersmentioning
confidence: 87%
“…All of these together point to the milieu of this relatively small region, where 3 physiologically distinct environments converge, as the culprit for the development of these cancers. Other external observations that lend further credence to this include the established etiopathogenetic association of other anatomic variations such as pancreatobiliary maljunction (supra-Oddi union of common bile duct with main pancreatic duct), leading to reflux and causing cancers of the gallbladder, bile ducts and pancreas 18,19,28,34 as well as the well-known anatomic association of gastro-esophageal junction cancers developing through reflux and Barrett metaplasia. This is also supported by the fact that "transitional" zones where different epithelial types and milieus converge (as in the peri-ampullary region) are particularly vulnerable to chemical alterations as is well known for endoectocervical transition zone in the uterus and hilar lung cancers where transformation of respiratory to squamous epithelium takes place.…”
Section: Association Of Low Union With Peri-ampullary Cancersmentioning
confidence: 87%
“…An important risk factor that pathologists ought to be aware of is the pancreaticobiliary maljunction, which is the supra‐oddi union of the common bile duct and the main pancreatic duct, allowing reflux of pancreatic enzymes to the gallbladder. Pancreaticobiliary maljunction accounts for 5–10% of GBCs both in the East and West, 14,15 and offers an invaluable model of anatomy‐induced carcinogenesis. It also bears a risk for bile duct cancers.…”
Section: Risk Factorsmentioning
confidence: 99%
“…It also bears a risk for bile duct cancers. The risk of carcinoma in such patients is so high that in a patient with this anomaly the gallbladder should be removed and examined entirely to rule out carcinoma 14,15 …”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muraki et al found that 8% of patients with GBC in the US had PBM (24/300), in Japan the situation is similar (15/171, 8.8%), but PBM is usually not diagnosed initially. 31 Hyvarinen et al reported that the estimated prevalence of PBM among patients with GBC was 17%. 32 Fujimoto et al observed that the incidence of GBC among PBM patients was 58% (7/12), and elevated bile amylase levels in PBM patients with serum amylase levels close to the upper limit of normal range seems may be related with GBC.…”
Section: Pancreatobiliary Maljunctionmentioning
confidence: 99%